2019
DOI: 10.3390/jcm8091418
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Tracking of Dental Pulp Stem Cells In Vitro and In Vivo Using Dextran-Coated Superparamagnetic Iron Oxide Nanoparticles

Abstract: The aim of this study was to track dental pulp stem cells (DPSCs) labeled with dextran-coated superparamagnetic iron oxide nanoparticles (SPIONs) using magnetic resonance imaging (MRI). Dental pulp was isolated from male Sprague Dawley rats and cultured in Dulbecco’s modified Eagle’s medium F12 (DMEM-F12) and 10% fetal bovine serum. Effects of SPIONs on morphology, viability, apoptosis, stemness, and osteogenic and adipogenic differentiation of DPSCs were assessed. Prussian blue staining and MRI were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…The cell viability was calculated at optical density of 570 nm on a microplate reader (Floustar Omega, BMG LabTech, Germany) (n=4) using the following formula (15), while Ac and Ab were considered as the absorbance in the control and blank wells: %Survival rate=A sample-(Ab×Ac-Ab)×100.…”
Section: Methodsmentioning
confidence: 99%
“…The cell viability was calculated at optical density of 570 nm on a microplate reader (Floustar Omega, BMG LabTech, Germany) (n=4) using the following formula (15), while Ac and Ab were considered as the absorbance in the control and blank wells: %Survival rate=A sample-(Ab×Ac-Ab)×100.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cryopreserved in 10% (V/V) dimethyl sulphoxide (DMSO; MP Bio USA), 50% (V/V) fetal bovine serum and 40% DMEM, at a density of 1×10 6 cells/mL until use. 22 …”
Section: Methodsmentioning
confidence: 99%
“…The cDNA was synthesized by 1,000 ng total RNA in a first strand cDNA synthesis reaction using RevertAid™ First Strand cDNA Synthesis kit (Thermo Fisher Scientific, USA). 22 …”
Section: Methodsmentioning
confidence: 99%
“…reported that SPIONs below the dosage of 25 mg mL −1 showed no adverse effects on the differentiation properties of dental pulp stem cells. [ 121 ] Additionally, amine‐surface‐modified SPIONs at the same concentration reported no side effects on the adipogenic, osteogenic, and chondrogenic differentiation capacity of human adipose tissue‐derived stem cells. [ 122 ] Also, our previous study showed that FIONs at the optimal concentrations did not produce excess ROS and showed no adverse impacts on the multifunctional differentiation capacity of human placenta‐derived MSCs, including osteogenic, adipogenic, and chondrogenic differentiation.…”
Section: Challengesmentioning
confidence: 99%